Fundamental Analysis of Stock Price Changes in Pharmaceutical Subsector Companies Listed on the Indonesia Stock Exchange for the Period 2016 – 2020 - Nigita Ratnasari; Eko Diyah Nurkhayati (Dhana, 2024)
The aim of this research is to analyse the impact of Return On Assets (ROA), Return On Equity (ROE), and Earnings Per Share (EPS) on the stock prices of pharmaceutical companies listed on the Indonesia Stock Exchange. This study employs a quantitative approach. The data used are secondary data in the form of company financial reports obtained from the Indonesia Stock Exchange (IDX). The sample selection in this study used purposive sampling, which involves selecting samples based on specific criteria. The data analysis method applied is multiple linear regression analysis. The results of this study indicate that the independent variable ROE positively correlates with stock price prediction, as evidenced by a calculated t-value of 5.721, which is greater than the critical t-value of 2.02619. EPS also positively correlates with stock price prediction, with a calculated t-value of 2.004, which is slightly less than the critical t-value of 2.02619. However, the ROA variable negatively correlates with stock price prediction, with a calculated t-value of -4.273, which is less than the critical t-value of 2.02619. Return On Assets (ROA), Return On Equity (ROE), and Earnings Per Share (EPS) collectively have a significant impact on stock prices. From the regression coefficient test, it is concluded that 56% of the stock price can be explained by the independent variables. This study illustrates that the pharmaceutical subsector companies listed on the Indonesia Stock Exchange rely more on a strong capital structure to improve financial performance, with a focus on increasing stock prices.